ESTIMATION OF CARBON STOCKS IN DIFFERENT TYPES OF LAND COVER IN THE COAL MINING AREA, NUNUKAN DISTRICT - Arief Nugroho, Septian
Estimation of carbon stocks in each activity in the coal mining process is necessary as a base for post-mining reclamation plans. This study provides an overview of the value of carbon stocks stored in five different pools: aboveground biomass, litter, deadwood/woody debris; and soil in four types of land cover (primary forest, secondary forest, palm oil plantation and open land) at PT. Duta Tambang Rekayasa. The data-collection used in this study is vegetation analysis on 20 plots to estimate the carbon stock values. Multilevel plots are used to measure different life-form. The 20x20m plots are used to measures trees and necromass, 10x10m plots are used for poles, 5x5m plots are for saplings, and the 2x2m plots are for litter and understorey. Core sampler was used to collect carbon samples from the soil. Allometric method was used do estimate the value of aboveground biomass and deadwood/woody debris biomass, while destructive method was used for soil organic carbon and litter. The results showed that primary forest has the highest carbon stock value (417.68 tons of C/ha), followed by secondary forest (124.94 tons of C/ha), palm oil plantation (21.35 tons of C/ha) and open land (1.46 tons of C/ha). Tree species that contribute the largest value of carbon stocks are Shorea javanica (50.29 Ton C/Ha). Comparative value of each type of land cover and primary forest are; 100% (primary forest), 38.48% (secondary forest), 5.11% (palm oil plantation), and 0.35% (open land). Mining activities can eliminate 99.65% of the value of carbon stocks from primary forests.